Review: The Level of Organizational Commitment And Integrity From Gender Differences in The Teaching Professional - Agus Satriawan; Rina Anindita (Publisher Cv. Inara, 2021)
The present study was aimed to examine level in organizational commitment between different gender among lecturer’s profession. We hypothesized that female lecturer would tend to have higher organizational commitment compared to the male lecturer. Participants were 204 lecturers (103 males, 101 females). Data is processed by statistical t test with the results showing that the organizational commitment of the teaching profession in general is high. However, in contrast to the hypothesis we propose, male organizational commitment is higher than women.